Necator americanus and helminth co-infections: further down-modulation of hookworm-specific type 1 immune responses. - Stefan Michael Geiger; Neal Douglas Edward Alexander; Ricardo Toshio Fujiwara; Simon Brooker; Bonnie Cundill; David Joseph Diemert; Rodrigo Correa-Oliveira; Jeffrey Michael Bethony (Public Library of Science (PLoS), 2011)
Helminth co-infection in humans is common in tropical regions of the world where transmission of soil-transmitted helminths such as Ascaris lumbricoides, Trichuris trichiura, and the hookworms Necator americanus and Ancylostoma duodenale as well as other helminths such as Schistosoma mansoni often occur simultaneously.We investigated whether co-infection with another helminth(s) altered the human immune response to crude antigen extracts from either different stages of N. americanus infection (infective third stage or adult) or different crude antigen extract preparations (adult somatic and adult excretory/secretory). Using these antigens, we compared the cellular and humoral immune responses of individuals mono-infected with hookworm (N. americanus) and individuals co-infected with hookworm and other helminth infections, namely co-infection with either A. lumbricoides, Schistosoma mansoni, or both. Immunological variables were compared between hookworm infection group (mono- versus co-infected) by bootstrap, and principal component analysis (PCA) was used as a data reduction method.Contrary to several animal studies of helminth co-infection, we found that co-infected individuals had a further downmodulated Th1 cytokine response (e.g., reduced INF-γ), accompanied by a significant increase in the hookworm-specific humoral immune response (e.g. higher levels of IgE or IgG4 to crude antigen extracts) compared with mono- infected individuals. Neither of these changes was associated with a reduction of hookworm infection intensity in helminth co-infected individuals. From the standpoint of hookworm vaccine development, these results are relevant; i.e., the specific immune response to hookworm vaccine antigens might be altered by infection with another helminth.